Upaya Meningkatkan Prestasi Belajar Melalui Peningkatan Kecerdasan Spiritual Santri Pondok Pesantren - Kusuma, Wira Hadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2019)
The purpose of this study was to analyze efforts to improve learning achievement through increasing spiritual intelligence in increasing student learning achievement. The research method, this research is a field research with a qualitative approach, with data collection tools through interviews, observation and documentation. The results of the study, in general, that the spirituality of students has an impact on improving student learning achievement. This is done in 7 ways or efforts made by the Kiai and Ust, namely earnest (istiqomah), fasting a lot, performing night prayers, reading the Koran, accustoming ablution, leaving immorality, and should not be indiscriminate snacks. In conclusion, the increase in santri's spiritual intelligence has a positive impact on improving learning achievement. Keywords: Spiritual Intelligence, Learning Achievement, Santri Spiritualistas